Cuff-Method Thigh Arterial Occlusion Counteracts Cerebral Hypoperfusion Against the Push–Pull Effect in Humans - Xing, Changyang; Gao, Yuan; Wang, Xinpei; Xing, Wenjuan; Liu, Yunnan; Lei, Yujia; Zhang, Xing; Zhang, Shu; Yuan, Lijun; Gao, Feng (Frontiers in Physiology, 2021)
Exposure to acute transition from negative (-Gz) to positive (+Gz) gravity significantly impairs cerebral perfusion in pilots of high-performance aircraft during push-pull maneuver. This push-pull effect may raise the risk for loss of vision or consciousness. The aim of present study was to explore effective countermeasures against cerebral hypoperfusion induced by push-pull effect. Twenty healthy young volunteers (male, 21±1 year old) were tested during the simulated push-pull maneuver by tilting. Thigh cuff (TC) pressure of 200 mmHg was applied before and during simulated push-pull maneuver (-0.87 to +1.00 Gz). Beat-to-beat cerebral and systemic hemodynamics were measured continuously. During rapid -Gz to +Gz transition, mean cerebral blood flow velocity (CBFV) was decreased, but to a lesser extent in TC bout compared with in control bout (-3.1±4.9 vs. -7.8±4.4 cm/s, P<0.001). Similarly, brain-level mean blood pressure showed smaller reduction in TC bout than control bout (-46±12 vs. -61±13 mmHg, P<0.001). The systolic CBFV was lower but diastolic CBFV was higher in TC bout. The systemic blood pressure response was blunted in TC bout, along with similar heart rate increase, smaller decrease and earlier recovery of total peripheral resistance index than control during the gravitational transition. These data demonstrated that restricting thigh blood flow can effectively mitigate the transient cerebral hypoperfusion induced by rapid shift from -Gz to +Gz, characterized with remarkable improvement of cerebral diastolic flow.